SHOPEE PAYLATER LOANS REVIEWED OF KHES - Sarah Khairani Harahap; Ikhwanuddin Harahap (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The research problems are how to practice Shopee Paylater loans in Padang Sidempuan City and how to review the compilation of Sharia Economic Law on Shopee Paylater loans. religion teaches its people to have the nature of qanaah, not to have the related wasteful nature until learning the money to buy an item that does not get the benefit or necessary. In the compilation of Sharia Economic Law is mentioned qardh loans. In Article 615 KHES related to qardh, the customer may make additional or voluntary contributions to the lender as long as it is not promised in the transaction. The purpose of this study was to determine how the practice of Shopee Pay Later loans in the city of Padang Sidempuan and review based on the compilation of Sharia Economic Law.This research is field research that uses data collection techniques such as observation, interviews, and documentation. Then pick up books related to this research such as law books, journals, government publications, as well as sites or other sources that support this research. The result of this research is that Shopee Paylater can be accessed by all users by registering first. Then the user can directly do checkout by having an installment payment system of 3, 6, or 12 installments with a predetermined interest. The influence of the use of this feature has a consumptive impact on the community to become addicted to shopping or known as Shopaholic. Even the reprimand given by Shopee does not make some people a deterrent to loans. Based on a review of the compilation of Sharia Economic Law Against loans Shopee Paylater on e-commerce shows that the loan or qardh is not in accordance with article 609 KHES because in the compilation of Sharia Economic Law the borrower may provide additional payments or voluntary donations to the lender, but not agreed upon in the transaction.